Surfactant administration during spontaneous breathing via a thin endotracheal catheter - Martinelli, S.; Gatelli, I.; Proto, A. (Acta Biomedica Atenei Parmensis, 2013)
In the past two decades exogenous surfactant administration has been a cornerstone of therapy for preterm infants and is known to be effective either given prophylactically in the delivery room or later as selective therapy to infants with estabilished respiratory distress syndrome. Its introduction in neonatal practice in the early 90s was followed by a significant decrease in overall neonatal mortality.With the evolution and refinement of intensive care for preterm infants, the role of exogenous surfactant therapy is changing.The more widespread use of nasal continuous positive airway pressure (n-CPAP) as a primary mode of respiratory support means that many preterm infants now avoid intubation in the delivery room or in early post-natal life. Still, about 50% of them,will require intubation for surfactant delivery for evolving respiratory distress syndrome (RDS) during the course of hospitalization. In view of the difficulties and side effects that may be associated with intubation for surfactant delivery, less invasive ways of surfactant administration have been pursued.The rationale and the available evidences inherent the administration of surfactant via a thin endotracheal catheter during spontaneous breathing will be discussed.